Are we accurately estimating the potential role of pollution in the decline of species at risk in Canada? - Jenny L. McCune; Sheila R. Colla; Laura E. Coristine; Christina M. Davy; D.T. Tyler Flockhart; Richard Schuster; Diane M. Orihel (FACETS, 2019)
Pollution is a pervasive, albeit often invisible, threat to biodiversity in Canada. Currently, the Committee on the Status of Endangered Wildlife in Canada (COSEWIC) relies on expert opinion to assess the scope (i.e., the proportion of a species’ population that may be affected) of pollution to species at risk. Here, we describe a spatially explicit, quantitative method for assessing the scope of pollution as a threat to species at risk in Canada. Using this method, we quantified the geographic co-occurrence of 488 terrestrial and freshwater species and pollution sources and determined that, on average, 57% of the mapped occurrences of each species at risk co-occurred with at least one pollution source. Furthermore, we found a weak correlation between the scope of the threat of pollution as assessed by COSEWIC expert panels and the geographic overlap of species occurrences and pollution sources that we determined with our quantitative method. Experts frequently identified scope of pollution as absent or negligible even for species with extensive co-occurrence with pollution sources, especially vascular plants. Clearly, a quantitative approach is needed to make accurate estimates of the scope of pollution as a threat to species at risk in Canada.